Kinetics and mechanism of the thermal degradation of biopolymers chitin and chitosan using thermogravimetric analysis - Moussout, Hamou; Ahlafi, Hammou; Aazza, Mustapha; Bourakhouadar, Mohamed (Polymer degradation and stability, 2016)
In this work, the kinetics of thermal degradation of chitin and chitosan polymers were investigated by means of Fourier Transform Infrared Spectroscopy and thermogravimetric analyses in air atmosphere, under dynamic conditions in the range of 298–873 K. The kinetic parameters, such as the apparent activation energy (Ea) and pre-exponential factor (A) were determined using Ozawa–Flynn–Wall (OFW) and Kissinger–Akahira–Sunose (KAS) isoconversional methods. The experimental data were found, in the range of conversion fraction 0.1 < α <0.8, to be well described by the modified catalytic Sestak–Berggren (SB) model adapting the conversion function, f(α) = cαm(1−α)n with the adjusted values of m, n and c. It was found that the simulated curves issued from the model best fit those issued from the experimental data, indicating the same scission mechanism for the degradation of chitin and chitosan. It was found that the average value of Ea = 125 kJ/mol used in the simulated curves of chitin, Y (α) and Z (α), is comparable to those calculated by KAS and OFW, while for chitosan, it represents the mean value (Ea = 169 kJ/mol) between the values of Ea calculated by KAS (Ea = 191.61 kJ/mol) and OFW (Ea = 146.50 kJ/mol) methods.